Neoplastic diseases in families of breast cancer patients. Issue 8 (August 1994) - Tulinius, H; Olafsdottir, G H; Sigvaldason, H; Tryggvadottir, L; Bjarnadottir, K
Abstract : OBJECTIVE--To investigate whether the risk of cancer at all sites, and at individual sites other than breast, prostate, ovaries, and endometrium, is increased among relatives of breast cancer patients compared with the general population. DESIGN--A cohort of family members of breast cancer patients was established. The probands were chosen by year of birth or time of diagnosis. Any influence of knowledge of the cancer experience of the relatives has been avoided. The risk estimates are based on expected numbers computed from age and time specific incidence rates for the Icelandic population. SETTING--Iceland. SUBJECTS--The population of Iceland. MAIN OUTCOME MEASURES--Relative risks by degree of relatedness and age of proband. RESULTS--The relative risk of cancer at all sites is raised for males and females. This is more than expected based on the known familial risk of breast cancer, prostate, and ovarian cancer. The excess risk of breast, prostate, and ovarian cancer is confirmed, but not that of cancer of the endometrium. The risk of cancer of the pancreas in both sexes and the stomach and kidneys in females is significantly raised. No evidence was found for decreased risk for any cancer type. CONCLUSIONS--The risk of cancer at all sites in relatives of breast cancer patients is increased. In addition to the risk of breast, prostate, and ovarian cancer, the risk of pancreas cancer and cancer of the stomach and kidneys in females is raised, but the last mentioned observations need further confirmation.